Changes in photosynthetic performance and ABA levels under osmotic stress in drought tolerant and sensitive wheat genotypes - Guóth, Adrienn (Acta Biologica Szegediensis, 2008)
We investigated the effect of osmotic stress induced by 400 mOsm PEG 6000 on the photosynthetic parameters and the abscisic acid (ABA) levels in drought tolerant (Triticum aestivum L. cv. MV Emese) and sensitive (cv. GK Élet) wheat cultivars in seedling stage. Our aim was to find fast and sensitive laboratory methods for screening drought sensitivity of the genotypes. The water potential (Ψw) values, net CO2 assimilation, chlorophyll a (chla) fluorescence and ABA levels in leaves and roots were determined a function of increasing osmotic stress. Although the decline of Ψw was more significant in the leaves of the sensitive cultivar (cv. Élet), the effect of water stress on the PSII photochemistry was not more pronounced. The ABA levels increased earlier, from day 9 under osmotic stress in the sensitive cultivar, but the hormone contents of the leaves were higher in the tolerant cv. MV Emese. This suggests that the accumulation of the stress hormone, ABA is a first line of defence to osmotic stress.